Commercialisation of stem cells - Roberts, Gareth (Henry Stewart Talks, 2007)
Why use stem cells?, The IP problems of commercializing stem cell research, Ethics and commercialization, Selecting stem cells for commercial development, Producing cells for product development, Scale-up and quality issues, The promise of automation, Developing a product, Lung disease: the medical need and the approach, Simplifying the strategy by simplifying the product, R&D of a lung assist device for lung therapeutics, The key lesson for commercial development